2011
DOI: 10.1007/s11270-011-0913-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Heavy Metals Cu, Ni, Cd and Zn on the Growth and Reproduction of Epigeic Earthworms (E. fetida) during the Vermistabilization of Municipal Sewage Sludge

Abstract: In order to enhance the removal of heavy metals such as Ni, Cu, Zn and Cd from wastewater, different cow dung/sewage sludge ratios were tested to assess the effect of these metals on the adaptability of Eisenia fetida earthworms to the treatment process carried out in a typical plant located in Tamaulipas, Mexico. Two experimental water treatment setups were proposed. The first set of experiments was planned to determine the adequate sewage sludge/cow dung ratio(s), whereas the second arrangement was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Dominguez-Crespo et al (2012) also found increased reproduction of E. fetida with cow manure and they associated it with the increase of OM in the soil. The reason for this increase probably was the same as ours.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Dominguez-Crespo et al (2012) also found increased reproduction of E. fetida with cow manure and they associated it with the increase of OM in the soil. The reason for this increase probably was the same as ours.…”
Section: Discussionmentioning
confidence: 82%
“…The earthworms are sensitive to Cu and Zn (Onuoha and Worgu, 2011;Dominguez-Crespo et al, 2012). Some studies about the effect of the direct application of metals (salt forms) in soils, have proven the toxicity of Cu and Zn to E. andrei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions of microbial siderophores can increase labile metal pools and uptake by roots (Mench and Bes 2009 ;Ali et al 2013 ). Bacteria are an important factor of soil, because they have the ability to mineralize organic matter, improving bioavailability and effectiveness of nutrient uptake (Domínguez-Crespo et al 2012 ). Bacteria present in soil have a signifi cant impact on phytoremediation, especially those bacteria which belong to the plant growth-promoting rhizobacteria/bacteria (PGPR/ PGPB) group.…”
Section: Nimentioning
confidence: 99%
“…Through the ability to decompose organic matter, they take a signifi cant role in the distribution of generated energy, and also conversion of proteins from plant residues on the nitrogen dissolved in the acidic form or NH 4 + ions, which are more easily available forms for plants. In addition, mushrooms are involved in the circuit of inorganic components (Domínguez-Crespo et al 2012 ). Also through the presence of plant-fungus symbiosis, the plant becomes much more resistant to environmental stress (Khan 2005 ;Gamalero et al 2009 ;Rabęda et al 2011 ).…”
Section: Nimentioning
confidence: 99%